Hyperbaric Oxygen Therapy in Ischaemic Foot Ulcers in Type 2 Diabetes: A Clinical Trial - Perren, Sarah (Open Cardiovasc Med J, 2018)
BACKGROUND AND AIMS: Several treatment modalities and protocols for ischaemic foot ulcers are available. However, little consensus exists on optimal treatment. The aim of this study was to compare Standard Wound Care (SWC) alone vs. SWC with adjunct hyperbaric oxygen therapy (HBOT) in the treatment of ischaemic Diabetic Foot Ulcers (DFUs). PATIENTS AND METHODS: Twenty-six patients with Type 2 Diabetes Mellitus (T2DM) presenting with a newly diagnosed ischaemic foot ulcer were included. These were divided into group A (SWC with adjunct HBOT) and group B (SWC only). Participants were followed every week for 4 weeks and their ulcers were measured for their surface area and depth to assess any change in wound size. RESULTS: Both treatment arms succeeded in reducing ulcer area and depth (p<0.001). However, ulcer area (p<0.001) and depth (p<0.001) exhibited superior improvement in group A. CONCLUSION : Adjunctive HBOT appears to improve wound healing in ischaemic DFUs and merits further study.